Analytical and clinical performance evaluation of the Wantai chemiluminescence microparticle immunoassay on the Wan200 + analyzer for diagnosing HIV - Jianfeng Chen; Liyue Jiang; Ran Ju; Yitong Li; Fengtian Wang (Scientific Reports)
Abstract On September 1, 2019, China implemented the “Blood Station Technical Operation Procedures (2019 Edition),” specifying Enzyme-Linked Immunosorbent Assay (ELISA) and Chemiluminescent Immunoassay (CLIA) for serological testing. However, no CLIA HIV reagent has been approved for blood donor screening in China. This study evaluates the WT CMIA reagents for HIV screening in blood stations, providing evidence for their approval as a national screening tool. A controlled trial compared WT CMIA and ELISA reagents, as well as CLIA reagents from other manufacturers, through clinical experiments and reference serum panel testing. Evaluation metrics included precision, sensitivity, specificity, detection limit, method comparison, and reference range. Clinical Experiments: Among 10,470 blood donor samples, WT CMIA detected 100% of confirmed HIV-infected donors (42/42), compared to 97.62% for ELISA (41/42). CMIA and Wantai ELISA both had a specificity of 99.96%, Lizhu ELISA 99.98%. Kappa values between CMIA and ELISA methods were 0.90 and 0.92. Reference Serum Testing: Both CMIA and ELISA demonstrated 100% sensitivity (148/148). CMIA had a CV under 5%, while ELISA methods exceeded 5%. WT CMIA detected 97.03% of early HIV infections, compared to 93.07% for Roche and Abbott CLIA. Detection titers for HIV subtypes were not lower than 1:40, with a detection limit of 1.25 IU/mL for the P24 antigen, meeting WHO standards. WT CMIA shows high consistency with ELISA and superior sensitivity for early HIV detection, meeting WHO standards for blood donor screening in China.